The Quality of Electronic Student Worksheet on the Protists Concept to Improve Critical Thinking Skills at the High School Level - Amelia, Riska; Zaini, Muhammad; Arsyad, Muhammad (Islamic Journal of Integrated Science Education (IJISE), 2023)
The use of electronic student workhsheet as a support for learning the concept of protists has not been utilized optimally and has not trained students to think critically which is a skill that is much needed in facing challenges in the 21st century. This study aims to describe the effectiveness of the electronic student worksheet on the protista concept in improving students' critical thinking skills. The research subjects through the small group test in development research were four students of class X State Aliyah Madrasah Kapuas. The critical thinking skills instrument from Facione was used to explore this data. The data analysis technique of the effectiveness of expectations is percentage. The results showed that evaluation and inference skills had increased. Other critical thinking skills did not show improvement, but the categories were at least good, namely interpretation, analysis, explanation, and self-regulation. Thus, electronic student workhseet on the protist concept can improve critical thinking skills at the high school level and can be used as an alternative learning to train students' critical thinking skills